Digital chemiluminescence imaging of DNA sequencing blots using a charge-coupled device camera. - Karger, A E (1992)
Digital chemiluminescence imaging with a cryogenically cooled charge-coupled device (CCD) camera is used to visualize DNA sequencing fragments covalently bound to a blotting membrane. The detection is based on DNA hybridization with an alkaline phosphatase(AP) labeled oligodeoxyribonucleotide probe and AP triggered chemiluminescence of the substrate 3-(2'-spiro-adamantane)-4-methoxy-4-(3"-phosphoryloxy)phenyl- 1,2-dioxetane (AMPPD). The detection using a direct AP-oligonucleotide conjugate is compared to the secondary detection of biotinylated oligonucleotides with respect to their sensitivity and nonspecific binding to the nylon membrane by quantitative imaging. Using the direct oligonucleotide-AP conjugate as a hybridization probe, sub-attomol (0.5 pg of 2.7 kb pUC plasmid DNA) quantities of membrane bound DNA are detectable with 30 min CCD exposures. Detection using the biotinylated probe in combination with streptavidin-AP was found to be background limited by nonspecific binding of streptavidin-AP and the oligo(biotin-11-dUTP) label in equal proportions. In contrast, the nonspecific background of AP-labeled oligonucleotide is indistinguishable from that seen with 5'-32P-label, in that respect making AP an ideal enzymatic label. The effect of hybridization time, probe concentration, and presence of luminescence enhancers on the detection of plasmid DNA were investigated.